Juvenile justice - Williams, Barbara; Kurtis, Bill.; Kurtis Productions; Towers Productions, Inc.; Arts and Entertainment Network; A & E Home Video (Firm); New Video Group; History Channel (Television network) (New York, NY : A & E Home Video : Distributed by New Video Group, 2002)
One of the most disturbing modern trends is the soaring number of children who commit serious crimes. Looks at why kids are commiting so many crimes, what can be done to prevent them, and how the young perpetrators should be punished.
Documentary.
Host: Bill Kurtis.
Camera, Gene Cotton ... [et al.] ; tape editor, Neal Klaeser ; original music, Bryan Rheude.
"The History Channel."
Videodisc release of a c1994 episode from American justice.
DVD.
Keywords: Documentary television programs; Juvenile homicide; Juvenile justice, Administration of -- United States